Hubungan antara Kebiasaan Belajar dengan Hasil Belajar - Sainab, Sainab (Jurnal Pesona Indonesia, 2024)
This research was conducted at SMA Negeri 2 Majene to know the relationship between study habits and the biology learning outcomes of students in class XI MIA SMA Negeri 2 Majene. This type of research is correlational research. The population in this research were all students of class XI MIA SMA Negeri 2 Majene, totaling 180 people. The cluster random sampling technique used the Slovin formula to determine the sampling technique so that the sample used was 124 people. Data collection on study habits used questionnaires that were distributed directly and data collection on learning outcomes using semester test scores (cognitive scores) of students. class XI MIA in biology lessons in the even semester of the 2021/2022 student year. The research data were analyzed using SPSS 23. The results of this study were there is a positive and significant relationship between study habits and biology learning outcomes for students of class XI MIA SMA Negeri 2 Majene as indicated by the value of the correlation coefficient (0.608) and the value of Sig. (0.000) <0.05.